Mobile commerce application development - Chen, Lei-da, 1973-; Skelton, Gordon W. (Hershey PA : IRM Press, 2005)
'This book provides in-depth coverage of the various tools and techniques for developing wireless and mobile applications'--Provided by publisher
Includes bibliographical references and index
Keywords: Mobile commerce; Wireless communication systems; Mobile communication systems